SW Iberia Variscan Suture Zone: Oceanic Affinity Units - Quesada, Cecilio (2020)
The geology of SW Iberia records a sequence of geologic events from the Cambrian-Early Ordovician rifting and subsequent passive margin development along the southern flank of the Rheic Ocean, to onset of oblique (sinistral) subduction in the Devonian, followed by oblique terrane accretion, ocean closure/continental collision and orogenic collapse. As a result, SW Iberia contains the southernmost exposure of the Pangean suture in the European Variscides. This suture zone is characterized by a belt of dismembered oceanic-related rocks and HP metamorphic complexes which are tectonically juxtaposed with the Gondwanan passive margin to the north (OMZ) and with the exotic South Portuguese Terrane to the south, which is thought to be either a remnant of Avalonia or Meguma.